Analisis Penyebaran Hoax Di Media Sosial Dan Dampaknya Terhadap Masyarakat - Yopita Desriana Butar (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The spread of hoaxes on social media has become a serious problem in society. This research aims to analyze the factors that cause the spread of hoaxes, the characteristics of hoax content, a well as their impact on society. The research method used is the study of literature and content analysis from various online news sources. The results showed that the main factors of the spread of hoaxes were lack of digital literacy., economic motivation, and political polarization. Hoax content generally spreads quickly, has sensational titles, and contains inaccurate information. The impact of hoaxes on society includes confusion, social conflict, and a decline in public trust. This research concludes that comprehensive efforts from the government, media, and the public are needed to overcome the hoax problem. This research aims to analyze the causes, patterns of spread, and the impact of hoaxes on social media on the community. The research methods used are literature studies and content analysis from various trusted sources. Patterns of spreading hoaxes generally utilize sicial media algorithms to achieve a wide reach quickly. The negative impact of hoaxes on society is very diverse, ranging from triggering social confilcts, affecting public opinion, to threatening political stability and national security. This shows the urgency of handing hoaxes comprehensively, involving the role of government, social media platforms, and the public.